Coming Together: R&D and Children’s Entertainment Company in Designing APPs for Learning Early Math - Mera, Carlos; Ruiz, Gonzalo; Aguilar, Manuel; Aragón, Estíbaliz; Delgado, Cándida; Menacho, Inmaculada; Marchena, Esperanza; García Sedeño, Manuel; Navarro, Jose I. (Frontiers in Psychology, 2019)
Information and Communication Technologies (ICT) have an increasing influence on the way of interaction, learning and life. The increase in teaching and learning methodologies that are mediated by ICT in the field of education and in the domestic settings encourages the design of new effective technological tools, supported by scientific research and development to improve student learning. The challenge psychology facing education is to promote those technologies and make them available to the education community. Technologies also would produce attractive items for users and realistic commercial issues for businesses. This also allows an effective transfer for scientific work, providing visibility to Research & Development. In this paper, we present different applications (APPs) designed for tablets and smartphone devices, adapted to the different operating systems (IOS, Android, Windows). APPs are designed to drill the cognitive fundamentals associated with early math learning for students aged 4 to 7 years. In order to create a competitive professional tool, an enterprise agreement with the children's entertainment company Babyradio (https://babyradio.es/) was established. This radio station along with an educational content developers’ company provided us graphic, animation and multimedia elements. Babyradio has also helped us with research results dissemination via website. This study contributes to the development of mathematics skills in children, aged 4 to 7 years, so that they can successfully meet the mathematics school requirements; it also contributes to encouraging a more positive attitude towards mathematics. This study also suggests that after an empirical validating of these APPs, teachers, parents, the education system and software and educational content developers’ companies would manage verified instructional APPs, with a more realistic commercial perspective.